2020
DOI: 10.1111/1462-2920.15031
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐regulated susceptibility of tomato fruit toColletotrichumandPenicilliumrequires differential mechanisms of pathogenicity and fruit responses

Abstract: Summary Colletotrichum gloeosporioides and Penicillium expansum cause postharvest diseases in tropical and deciduous fruit. During colonization, C. gloeosporioides and P. expansum secrete ammonia in hosts with low sugar content (LowSC) and gluconic acid in hosts with high sugar content (HighSC), respectively, as a mechanism to modulate enhanced pathogenicity. We studied the pathogens interactions with tomato lines of similar genetic background but differing in their sugar content. Colletotrichum gloeosporioide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…For example, spermine treatment resulted in higher levels of glucose, fructose and sucrose in Arabidopsis, as well as higher resistance to B. cinerea . Moreover, Colletotrichum gloeosporioides showed enhanced colonization in tomato fruit with low sugar content ( Ziv et al, 2020 ). Acetic acid suppresses the growth of C. gloeosporioides directly, and lowers the rate of infection in strawberries ( Kang et al, 2003 ; Weber et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, spermine treatment resulted in higher levels of glucose, fructose and sucrose in Arabidopsis, as well as higher resistance to B. cinerea . Moreover, Colletotrichum gloeosporioides showed enhanced colonization in tomato fruit with low sugar content ( Ziv et al, 2020 ). Acetic acid suppresses the growth of C. gloeosporioides directly, and lowers the rate of infection in strawberries ( Kang et al, 2003 ; Weber et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acidifying or alkalinizing pathogens decrease or increase the pH around their infection site, respectively (Prusky et al 2016 ). While various fungi employ different strategies, the specific fungal response is also much dependent on carbon and nitrogen availability (Bi et al 2016 , Ziv et al 2020 , Van Laethem et al 2021 ).…”
Section: Crops Protection: Ph-dependent Pathogenicity and Possible In...mentioning
confidence: 99%
“…Moreover, the specific gene responsive profiles for the two host lines differed significantly, which depended on the sugar level. The authors suggested that such differential response patterns may contribute to the differential host ranges for both pathogens (Ziv et al 2020).…”
Section: Sugar Metabolism Involved In Responses To Biotic Stressmentioning
confidence: 99%